Arah Baru Pendidikan Islam di Era Digital - Alfinnas, Shulhan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
This article is aimed to discuss the formulation of Islamic education in digital era and the out come intended to be gained throughout that education. By emerged digital era explosively, students generally since beginning become native digital, know well how to use digital device properly and easily conversely the majority of adults become digital native who do not really afford utilizing technology. Setting of Islamic education should be designed according to life style of that era’s pupils. This treatise is a synthetic though based on liberary research to explore prior findings and thinkings to forulize new terms as respond to the chllange and the opportunity in technology life. There are tow kinds of new synthetic though should be implemented to encourage Muslim generation; digitalizing the subjects of Islamic education and boosting them to reach hasanah in life wheater present and hereafter.